PERBANDINGAN MENGGUNAKAN MODEL PEMBELAJARAN COOPERATIVE TIPE TALKING STICK DENGAN MODEL PEMBELAJARAN TIPE MAKE A MATCH TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 9 KOTA JAMBI - Pratiwi Indah Sari, Rizki Amaliah, (SJEE (Scientific Journals of Economic Education), 2017)
This study aims to find out how the results of student learning using the learning model of talking stick and make a match learning model on economic subjects of capital market subject in class XI IIS SMA Negeri 9 Kota Jambi. The results showed student learning outcomes in class XI IIS 5 on the subject of capital market capital economics at SMA Negeri 9 Kota Jambi at the time of pre-test using the learning stick talking model obtained the highest learning result of 55.00, while using model make a match of 67.50. This means the pre-test when using make a match is higher than the talking stick learning model. Meanwhile, at the time of post-test using the talking stick learning model obtained the highest learning result of 50.00. Meanwhile, using make a match model of 77.50. This means the pre-test when using make a match is higher than the talking stick learning model.Kata Kunci : Learning Model, Talking Stick, Make a Match.